STATCOM Application for Reactive Power Compensation On Distribution of PLTMH Curug Muncar - Ghoni Musyahar; Muhammad Haddin; Arief Marwanto (Journal of Telematics and Informatics, 2020)
Among the sources of electrical energy used in remote areas or mountains are using micro hydro power plants (PLTMH). The problem that arises in PLTMH Curug Muncar is the low power factor (cos ϴ) in the distribution. The power factor measured in users / consumers is an average of 0.7. One of the reasons for this is the varied type and use of loads on consumers, resulting in waste reactive power.               As an alternative solution to these problems is to compensate for electrical power to load changes that are very dynamic. From the reference, it shows that the Static Synchronous Compensator (STATCOM) is the most effective reactive power compensator.               STATCOM is located in the position between the generator and load variation. The reactive power settings by STATCOM occur by comparing the value of the terminal voltage between STATCOM and the system. If the STATCOM voltage is lower than the system, the STATCOM will absorb reactive power from the system. Meanwhile, if the STATCOM voltage is higher than the system, the STATCOM will generate reactive power to the system               STATCOM is able to compensate for reactive power with a very fast time (0.3 seconds) and is able to absorb or provide reactive power to the distribution. STATCOM is able to change cos θ from 0.7 to 0.93. The repaired voltage is close to the given Vrms value. Keywords: PLTMH. STATCOM, Reactive Power